TECHNOLOGY-ENHANCED MATERIALS DEVELOPMENT FOR PROMOTING COMMUNICATIVE COMPETENCE THROUGH “UNLIMITED POWER” BOOK: A FLIPPED CLASSROOM APPROACH - Nilufarkhon Shokirova (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article presents the design and rationale of a technology-enhanced teaching material based on Anthony Robbins’ book Unlimited Power for upper secondary English language learners. The material is grounded in six principles of language acquisition, including authenticity, affective and cognitive engagement, positive attitude development, utilization of mental resources, language awareness, and communicative opportunities. Designed for B1+/B2 learners aged 15–16, the lesson adopts a Flipped Classroom approach and integrates digital tools such as Actively Learn, Ideaboardz, Hypothes.is, Wakelet, Edpuzzle, and Write & Improve. The activities promote the development of integrated language skills through collaborative learning, critical thinking, reflective writing, and project-based tasks. By engaging with authentic content and meaningful communication, learners enhance their communicative competence, digital literacy, creativity, and autonomous learning skills. The material also encourages personal growth and motivation through exposure to inspiring real-life stories and self-development concepts, creating a learner-centered and technology-rich educational environment.